Traumatic Pasts in Asia : History, Psychiatry, and Trauma from the 1930s to the Present. - Micale, Mark S. (Berghahn Books, Incorporated, 2021)
In the early twenty-first century, trauma is seemingly everywhere, whether as experience, diagnosis, concept, or buzzword. Yet even as many scholars consider trauma to be constitutive of psychological modernity or the post-Enlightenment human condition, historical research on the topic has overwhelmingly focused on cases, such as World War I or the Holocaust, in which Western experiences and actors are foregrounded. There remains an urgent need to incorporate the methods and insights of recent historical trauma research into a truly global perspective. The chapters in Traumatic Pasts in Asia make just such an intervention, extending Euro-American paradigms of traumatic experience to new sites of world-historical suffering and, in the process, exploring how these new domains of research inform and enrich earlier scholarship.
Description based upon print version of record.
Keywords: Psychic trauma -- Asia -- History -- Case studies.; Cultural psychiatry -- Asia -- Case studies.; Asia -- History -- Psychological aspects -- Case studies.; Traumatisme psychique -- Asie -- Histoire -- Études de cas.; Ethnopsychiatrie -- Asie -- Études de cas.; Asie -- Histoire -- Aspect psychologique -- Études de cas.; HISTORY / Asia / General.; Cultural psychiatry; Psychic trauma; Psychological aspects; Asia; History: 20th Century to Present, Memory Studies, Medical Anthropology.; Electronic books.; Case studies; History